VD_FINDINFO HC / 2011 / 526 vom 5. Juli 2011 - VD Tribunal cantonal (2011)
ADMISSION DE LA DEMANDE, IDENTITÉ, PROCÉDURE, DÉCISION D'IRRECEVABILITÉ | 209 CPC (CH), 221 CPC (CH), 308 al. 1 let. a CPC (CH), 310 CPC (CH), 405 al. 1 CPC (CH), 59 al. 1 CPC (CH)